Pengaruh Latihan Jump To Box Terhadap Kemampuan Heading - ikhwanul arifan; Afrizal s; Eri Barlian (Universitas Negeri Padang, 2020)
This type of research is artificial experiments, this research aims to know the extent of the influence of exercise Jump To Box against the ability of the Heading, (Experimental Study on Soccer Club athlete The son of Pasaman).The population in this research is the son of The Club's soccer athletes Pasaman amounted to 43 people. This research sample taken from junior athletes as much as 20 people, the technique of taking sample by way of Porposive Sampling. The sample in this research is the junior athletes Football athletes is incorporated in the Football Club The son of Pasaman. The hypothesis presented in this study is an exercise Jump To Box give influence on the ability of the Headings on the Football Club's athletes The son of Pasaman.Data analysis uses the t-test, the results of the processing of data is 1) based on table t distribution with degrees of freedom (dk) n-1 (20-1 = 19) significant levels of 0.05, then retrieved the table t = 2,093. So t count it = t table > 6,734 > 2,093 then Ho in decline while the Ha is received. In conclusion, there is a significant influence of exercise Jump To Box against the ability of the Heading